Employment Factors Associated With Long Working Hours in France - Isabelle Niedhammer; Elodie Pineau; Sandrine Bertrais (Elsevier, 2023)
The objectives of the study were to explore the employment factors associated with long working hours, known as a risk factor for various health outcomes. The study relied on the national representative data of the 2013 French working conditions survey and a study sample of 23,378 full-time employees. Long working hours were defined by the threshold of 48 hours a week following the European Working Time Directive. The prevalence of long working hours was higher among men (13.5%) than among women (8.5%). Employees of the private sector, with permanent work contract, in small companies, and men in the services had a higher prevalence of exposure. This prevalence increased with educational and occupational levels. Our findings may help decision-makers to define preventive strategies. More research is needed to improve our knowledge of the employment factors associated with long working hours, as there may be strong differences between countries.